STUDENTS’ PERSPECTIVE OF USING GOOGLE CLASSROOM AS THE LEARNING MANAGEMENT SYSTEM FOR STUDENTS’ WRITING SKILL - Hadijah Hadijah (Wiralodra English Journal, 2023)
This study aims to describe the students’ perspective toward the use of Google Classroom; 2) to describe how Google Classroom was applied in teaching writing. This qualitative study was conducted in the first semester of the law department of Universitas Muhammadiyah Bima. It was qualitative research with five participants. The theme-based analysis was used in this study. The finding showed that Google Classroom has affected the students' attitudes toward writing skills. The data from all the participants have proved that there has been significant improvement such as 1) writing enthusiasm; 2) effectiveness of timeliness; 3) easily for access to the material; 4) practicality for writing tests; 5) efficiency of google classroom for students writing. They have shown positive and negative attitudes which affected their achievement in writing. The negative aspects that appeared were the students were less confident seeing their names on the last list which means that their scores were among the lowest. Drawing on the findings, the Google Classroom application can be used to teach writing skills because it is more practical than traditional methods. This study suggests further investigation into the wider aspect of the effectiveness of Google Classroom in teaching writing.